The Development of a Mindful Explorer Learning Model to Enhance Emotional Regulation in Children Aged 4–5 Years - Miranti Rachmawati; Nita Priyanti; Debie Susanti (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aimed to develop and examine the feasibility and effectiveness of the Mindful Explorer learning model in improving emotional regulation in children aged 4–5 years. The study employed a Research and Development (R&D) approach using the ADDIE development model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were children aged 4–5 years at TK Negeri Pembina Purwakarta. The experimental group consisted of 10 children who received learning activities using the Mindful Explorer model. Data were collected through observations, interviews, expert validation, and assessment sheets. The results of expert validation indicated that the model was highly feasible, with a validation score of 95.56%. This result shows that the model meets the required standards in terms of content suitability, learning methods, media, evaluation instruments, and learning objectives. The effectiveness test showed an improvement in children’s emotional regulation after the implementation of the Mindful Explorer model. Based on the N-Gain calculation, the average N-Gain score was 0.55 (moderate category), with a percentage increase of 31.46% from the pretest to the posttest. The improvement was reflected in children’s ability to recognize emotions, control emotional responses, and express feelings more adaptively during learning activities. Therefore, the Mindful Explorer learning model is considered highly feasible and effective as an innovative learning approach to support emotional regulation development in early childhood.